2020
DOI: 10.5093/pi2019a14
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Brief Intervention Based on an Incremental Theory of Personality in the Prevention of Adolescent Dating Violence: A Randomized Controlled Trial

Abstract: Dating violence (DV) is an important, prevalent problem in adolescence worldwide (Wincentak, Connolly, & Card, 2017). It includes any act of physical, emotional, or sexual violence that can take place in person or electronically (Centers for Disease Control and Prevention, 2016). The recent meta-analytic review of teen DV prevalence rates by Wincentak et al. (2017) showed an overall rate of 20% and 9% for physical and sexual aggression, respectively. Adolescents who are involved in violent dating relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 48 publications
0
25
1
5
Order By: Relevance
“…The same effect is also evident in the results reported by Fernandez-Gonzalez et al (2020). 33 De la Rue Joshua, Polanin, Espelage & Pigott (2014) 44 stress the importance of time lapses in behavior modification: changes in behaviors require time and the development of socio-emotional skills for coping with conflicts within the couple. It may be that students simply do not have the opportunity to put what they have learned into practice in the short time that elapses between the completion of the programs and the post-test evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same effect is also evident in the results reported by Fernandez-Gonzalez et al (2020). 33 De la Rue Joshua, Polanin, Espelage & Pigott (2014) 44 stress the importance of time lapses in behavior modification: changes in behaviors require time and the development of socio-emotional skills for coping with conflicts within the couple. It may be that students simply do not have the opportunity to put what they have learned into practice in the short time that elapses between the completion of the programs and the post-test evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…31 In the same line, a more recent study carried out with 604 Spanish adolescents, found positive correlations of cyber dating violence with depressive mood and cyber bullying victimization both in boys and girls, and with loneliness in girls. 32 The need for early prevention is therefore evident 29,[33][34][35][36] and there is a broad consensus regarding the fact that said prevention should begin before adulthood. [37][38][39][40][41][42] In this sense, numerous prevention programs have been developed over recent decades [43][44][45][46] which can basically be divided into two types: specific and universal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these interventions have shown impressive results because they are frequently short-term (often single sessions of one hour) and produce lasting changes in behavior. Thus, many wise interventions have been shown to improve academic performance (Brisson et al, 2017), social integration of ethnic minority youth (Brannon & Walton, 2013), and reduce depression (Miu & Yeager, 2015) and aggressive behavior (Calvete, Fernández-Gonzalez, et al, 2019;Fernández-González et al, 2020) .…”
Section: Article In Pressmentioning
confidence: 99%
“…The study also takes a step forward in validating two less commonly recognised risk factors for engaging in cybercrime and cyber-deviance, namely general normative beliefs about aggression and moral disengagement. Early intervention targeting these factors could be made by institutions and caregivers (e.g., schools, parents and social workers) to reduce the risk of adolescents engaging in cybercrime and victimisation [ 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%